A Practical ECG Criterion to Unmask Left Accessory AV Connections in Patients With Subtle Preexcitation. (16th July 2015) - THOMPSON, J. JENKINS; SHAH, JIGNESH; CHARNIGO, RICHARD; TACKETT, ANDREA; DARRAT, YOUSEF H.; BAILEY, ALISON; DELISLE, BRIAN; KAKAVAND, BAHRAM; DI BIASE, LUIGI; NATALE, ANDREA; MORALES, GUSTAVO; ELAYI, CLAUDE S.
New ECG Criteria for Left‐Sided AV Connections Background Accessory AV‐connections capable of antegrade conduction need to be recognized because of the potential for life‐threatening arrhythmias. However, the preexcited ECG pattern may be subtle, especially among left‐sided AV‐connections. We explored whether additional ECG criteria might help identify left‐sided AV‐connections. Methods We analyzed 156 patients who underwent an electrophysiology study (EPS) and ablation for paroxysmal supraventricular tachycardias (PSVT). Patients were divided into 2 groups: those with left‐sided AV‐connections (Group 1) and all other PSVT (Group 2). Various ECG parameters were compared before and after ablation in both groups. Results The EPS identified left‐sided AV‐connections among 43 patients (Group 1) and excluded it among 113 (Group 2). Baseline ECG in Group 1 demonstrated obvious preexcitation among 24/43 patients (55.8%), the remaining 19/43 missing obvious preexcitation. R/S ratio > 0.5 in V1 was noted in 38/43 (88.4%) patients in Group 1 before ablation (median 1.00; IQR 0.58–2.20), including 16/19 (84.2%) patients lacking obvious left‐sided AVconnections. Conversely, only 10/113 (8.8%) patients in Group 2 had R/S ratios in V1 ≥ 0.5 (0.20; 0.10‐0.31), P < 0.0001. After ablation, the R/S ratio decreased significantly in Group 1 (0.29; 0.17–0.45), P < 0.0001. Thus, a combined criterion of classic preexcitation or R/S ratio ≥ 0.5 on ECG identified 40/43 left‐sided AV‐connections (sensitivity 93.0%). The negative predictive value of this combined criterion was 103/106 (97.2%). Conclusions In symptomatic patients, combining the R/S ratio (≥ 0.5) in lead V1 with the classic preexcitation pattern on ECG markedly improved the sensitivity to diagnose left‐sided AV‐connections. This ratio may be particularly useful among patients lacking obvious preexcitation.